Commercialization strategy and internationalization outcomes in technology-based new ventures - Symeonidou,N; Bruneel,J; Autio,E (Journal of Business Venturing, 2017)
Advances in business process outsourcing and open innovation practices have made the choice of techno logy commercialization strategy increasingly relevant for technology-based new ventures. We investigate effects of intellectual property (IP)-based, product-based, and hybrid (both product and IP) commercialization strategies on internationalization propensity and intensity in technology-based new ventures. We find that new ventures adopting a product-based commercialization strategy are less likely to internationalize than those with hybrid or IP-based strategies. In addition, new ventures using IP-based commercialization strategies exhibit higher international intensity after foreign market entry than those with hybrid and product-based strategies. These findings provide novel insights into the dependence on external resources associated with different types of commercialization strategy.